2014
DOI: 10.1021/ol503410e
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Hydroxylation of Aliphatic sp3 C–H Bonds Using a Ketone Catalyst and Aqueous H2O2

Abstract: The first ketone-catalyzed method for the oxidation of aliphatic C-H bonds is reported. The reaction conditions employ aryl trifluoromethyl ketones in catalytic amounts and hydrogen peroxide as the terminal oxidant. Hydroxylation is stereospecific and chemoselective for tertiary over secondary C-H bonds. A catalytic cycle invoking a dioxirane as the active oxidant is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…We recently explored the possibility that peptide-based ketones 5,6 might also be effective catalysts for oxidation, perhaps for both epoxidation and C–H hydroxylation reactions. 7,8 In an earlier study, for example, we found that a peptide-based trifluoromethyl ketone exhibited good catalytic properties, such that certain olefins could undergo epoxidation with enantiomeric ratios of up to 91:9 and good yields with use of 10 mol% of the catalyst (Figure 1b). 6 However, certain limitations were encountered, including the compatibility of an N -terminal amino acid residue as the moiety carrying the trifluormethyl ketone as the catalytic side chain.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…We recently explored the possibility that peptide-based ketones 5,6 might also be effective catalysts for oxidation, perhaps for both epoxidation and C–H hydroxylation reactions. 7,8 In an earlier study, for example, we found that a peptide-based trifluoromethyl ketone exhibited good catalytic properties, such that certain olefins could undergo epoxidation with enantiomeric ratios of up to 91:9 and good yields with use of 10 mol% of the catalyst (Figure 1b). 6 However, certain limitations were encountered, including the compatibility of an N -terminal amino acid residue as the moiety carrying the trifluormethyl ketone as the catalytic side chain.…”
Section: Introductionmentioning
confidence: 87%
“…p -Fluoroarene substitution, for example, demonstrated by Hilinski to be advantageous in ketone-catalyzed C–H hydroxylation reactions. 7 The successful synthesis of these unusual compounds, and the demonstration of their suitability as competent catalysts for olefin epoxidation is the subject of this report.…”
Section: Introductionmentioning
confidence: 97%
“…[78] Although the authors demonstrated the feasibility of catalysis, this methodw as limited only to specific substrates, which were oxidized with moderate conversions. [78] In 2017, after extensive investigation, they reported a second-generation approachtoketone-catalyzed hydroxylation that addresses these limitations. [79] Indeed, the hydroxylation of the CÀHb ond wasa ccomplished by treatment with ac ommerciallya vailable alkyl trifluoromethyl ketone 48 combined with oxone as oxidant(Scheme20).…”
Section: Site-selective Càhbond Oxyfunctionalization In Total Synthesmentioning
confidence: 99%
“…Trans-decahydronapthalen-9-ol were prepared according to literature methods. 10 Under an N2 atmosphere, a round-bottom flask was charged with a chromium trioxide (0.610 g, 6.10 mmol, 2.96 equiv), CH2Cl2 (3 mL) and CH 3 CN (9 mL). The mixture was stirred vigorously for 20 min and then cooled to -40 °C.…”
Section: Synthesis Of Trans-decahydronapthalen-9-ol (Trans-1)mentioning
confidence: 99%